2020
DOI: 10.7150/ijbs.37906
|View full text |Cite
|
Sign up to set email alerts
|

TIPE regulates VEGFR2 expression and promotes angiogenesis in colorectal cancer

Abstract: Background: Metastasis is the leading cause of death in colorectal cancer (CRC) patients. It is regulated mainly by tumor cell angiogenesis, and angiogenesis is caused by the binding of vascular endothelial growth factor (VEGF) to vascular endothelial growth factor receptor 2 (VEGFR2). Tumor necrosis factor--induced protein 8 (TNFAIP8, hereto after TIPE) plays an important role in tumorigenesis, development, and prognosis. However, the relationship between TIPE and VEGFR2 in CRC angiogenesis and the mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 40 publications
2
47
0
Order By: Relevance
“…VEGFR-2 mediates the main physiological functions of VEGF. VEGF, the vascular permeability factor (VPF), is an essential and crucial growth factor for vascular endothelial cells, and plays various roles in cardiovascular system ( Wang et al, 2019 ), central nervous system ( Bellon et al, 2010 ; Luck et al, 2019 ), hematopoiesis ( Hooper et al, 2009 ), development ( Karaman et al, 2018 ), and tumorigenesis ( Volz et al, 2020 ; Zhong et al, 2020 ). Despite having so many physiological functions, the main physiological functions of VEGF on endothelial cells are almost all achieved by activating VEGFR-2, including stimulating endothelial cell proliferation, increasing vascular permeability, and chemotaxis to endothelial cells, etc.…”
Section: Vegfr-2 Physiological Functions and Pathological Rolesmentioning
confidence: 99%
“…VEGFR-2 mediates the main physiological functions of VEGF. VEGF, the vascular permeability factor (VPF), is an essential and crucial growth factor for vascular endothelial cells, and plays various roles in cardiovascular system ( Wang et al, 2019 ), central nervous system ( Bellon et al, 2010 ; Luck et al, 2019 ), hematopoiesis ( Hooper et al, 2009 ), development ( Karaman et al, 2018 ), and tumorigenesis ( Volz et al, 2020 ; Zhong et al, 2020 ). Despite having so many physiological functions, the main physiological functions of VEGF on endothelial cells are almost all achieved by activating VEGFR-2, including stimulating endothelial cell proliferation, increasing vascular permeability, and chemotaxis to endothelial cells, etc.…”
Section: Vegfr-2 Physiological Functions and Pathological Rolesmentioning
confidence: 99%
“…PlGF, VEGF-A, and VEGF-B are required for angiogenesis (Takahashi and Shibuya, 2005). VEGF-A (also known as VEGF) is the major member of the VEGF family and promotes angiogenesis via binding to VEGF receptor-2 (VEGFR-2) (Zhong et al, 2020). VEGF-B, functionally and structurally related to VEGF-A and PlGF, regulates the bioavailability of VEGF-A (Olofsson et al, 1996).…”
Section: The Role Of Inflammatory Cytokines In Angiogenesis After Is Vegfmentioning
confidence: 99%
“…Studies have found that TIPE is highly expressed in pancreatic cancer, gastric cancer, endometrial cancer and other tumour cells, regulating the growth, proliferation, migration and invasion of tumour cells. [29][30][31] The TIPE protein was found to be significantly overexpressed in colon cancer tissues compared with tumour-adjacent tissues and was associated with the degree of malignancy of the tumour. 32 Zhong et al detected the relative mRNA expression levels of TIPE family members in tumour and adjacent tissue samples of patients with colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%